Forages research in Malawi: Take away from a national seminar - Homann-Kee Tui, Sabine; Chiumia, Daniel; Kawonga, Bettie (International Institute of Tropical Agriculture, 2024)
Multipurpose forages hold significant potential for both smallholder and commercial farmers in Malawi, yet their development remains underexplored. With growing demand for livestock products and diminishing natural forage resources, enhancing livestock performance through improved forages and feed can bolster livelihoods, income, environmental sustainability, and nutrition. Effective partnerships are key to advancing this agenda. To support this, a national technical working group on forages was proposed, initially facilitated by the Alliance of Bioversity International and CIAT (Alliance-CIAT), with support from Lilongwe University of Agriculture and Natural Resources (LUANAR) and the Department of Agricultural Research Services (DARS).